A method for preparing aluminum silicon oxide using high-aluminum fly ash
The synchronous extraction and utilization of alumina and silicon oxide are solved through high-alumina fly ash atmospheric pressure and low temperature technology, and the problems of single elements and high energy consumption in the existing technology are solved, and high-efficiency and low-cost aluminum-silicon oxide preparation and Comprehensive utilization of resources.
Patent Information
- Application Number
- CN202411073673.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The prior art has problems in the fly ash extraction process of alumina with single elements, long process flow, high energy consumption and low comprehensive utilization rate, and the failure to effectively utilize the silicon oxide resources in fly ash, resulting in waste of resources and Environmental pollution.
Using high-aluminum fly ash at normal pressure and low temperature technology, the pre-desilica of sodium hydroxide solution, dilute acid and medium-concentrated acid removal, combined with the acid recovery process, the synchronous extraction and utilization of alumina and silicon oxide are achieved, and the process is reduced. Energy consumption, improve the preparation efficiency and utilization rate of aluminum silicon oxide.
Achieve 100% utilization of high-aluminum fly ash, reduce process energy consumption and production costs, improve the comprehensive utilization rate of alumina and silicon oxide in fly ash, reduce secondary solid waste, and simplify the process flow, investment Cost reduction.
Smart Images

Figure CN118579815B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fly ash extraction technology, and in particular to a method for preparing aluminum silicon oxide using high-aluminum fly ash. Background Art
[0002] my country is short of bauxite resources and has a high degree of external dependence. In 2019 alone, my country imported about 90 million tons of bauxite, accounting for more than 60% of the annual consumption. The proven high-aluminum coal reserves in the Jungar coalfield in Inner Mongolia are 23.7 billion tons, accounting for about 74% of the country's high-aluminum coal. The fly ash produced by the combustion of high-aluminum coal contains about 35-53% alumina and 37-55% silicon oxide, which is a non-bauxite aluminum resource with great development value. At present, most of the fly ash formed by coal-fired power generation in the central and western regions of Inner Mongolia is simply piled up or used as a building material in a scattered manner, which not only pollutes the environment but also causes waste of resources. At the same time, the existing extraction technology has harsh reaction conditions, difficult multi-element synergistic extraction, resulting in low comprehensive utilization rate of fly ash, insignificant benefits, and difficult to promote and apply on a large scale. Therefore, how to use efficient extraction technology to utilize the aluminum and silicon elements in these high-aluminum fly ash resources has become a key issue for existing practitioners in the field. It can not only ensure the strategic security of my country's aluminum industry, but also benefit the local environmental protection and the development of a circular economy industry with important strategic significance.
[0003] In recent years, researchers have been continuously improving the technical process of extracting silicon aluminum oxides from high-aluminum fly ash. The main process types can be divided into pre-desiliconization-soda lime sintering method, acid method, ammonium sulfate sintering method, limestone sintering method, etc. Representative methods are soda lime sintering method and limestone sintering method. The limestone sintering method has the disadvantages of large slag phase flow and high energy consumption; the pre-desiliconization-soda lime sintering method is currently the only process method that can achieve industrial production, but the process has the problems of long process flow and high sintering energy consumption. CN 102583409 A relates to a method for producing mullite and calcium silicate using high-aluminum fly ash. The invention uses high-aluminum fly ash as raw material, removes iron through magnetic separation, and then performs pre-desiliconization reaction by alkali dissolution in a medium-temperature and medium-pressure reactor. After pickling with about 20% hydrochloric acid to remove sodium, calcium and iron, desiliconized fly ash is obtained. The desiliconized fly ash is calcined at high temperature (1200-1600°C) for 1-2 hours to obtain mullite refractory material. The desiliconized filtrate is causticized with lime milk to prepare calcium silicate. The technical solution of this invention requires medium-temperature and medium-pressure alkali dissolution (120°C) during the preparation process, and the raw materials need to be ball-milled, which has high requirements for the process and equipment; at the same time, the high-temperature sintering time is long, the energy consumption is large, the production cost is increased, and the final alumina content is low, which cannot meet the requirements of indicators such as M70.
[0004] On the other hand, the above-mentioned fly ash extraction alumina process technologies all have the problem of only utilizing the single element of alumina in fly ash, and the other main substance, silicon oxide, is treated as a by-product or solid waste, which actually forms a huge waste. Therefore, in order to effectively solve the above problems, the present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, which can simultaneously extract two substances, alumina and silicon oxide, from fly ash, which not only makes up for the technical defects of the prior art, but also has a wide source of raw materials, low energy consumption and low production cost, and high-aluminum fly ash adopts a normal pressure and low temperature process, and does not need to be treated at high temperature, medium temperature and other high-pressure sections; in the process of preparing the main product, the remaining components can be co-produced into mature industrial products, achieving 100% utilization of high-aluminum fly ash without generating secondary solid waste. Summary of the invention
[0005] In order to solve the above problems, the present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, the steps comprising: S1: pre-desiliconization of high-aluminum fly ash at normal pressure: the high-aluminum fly ash is subjected to normal pressure pre-desiliconization reaction with sodium hydroxide solution, and the solution after the reaction is filtered, washed and separated, and the solid phase is desiliconized fly ash, and the liquid phase is desiliconized alkali solution; S2: sodium removal: the desiliconized fly ash is mixed with dilute acid and then kept warm to remove sodium, and after the sodium removal is completed, the solid phase is sodium-removed desiliconized fly ash, and the liquid phase is a mixed salt solution of aluminum chloride, calcium chloride and sodium chloride; S3: impurity removal: the sodium-removed desiliconized fly ash is mixed with medium-concentrated acid and then subjected to normal pressure impurity removal, and after the impurity removal is completed, it is filtered and washed, and after the impurity removal is completed, the solid phase is deep desiliconized fly ash, and the liquid phase is a mixed solution of aluminum chloride salt and ferric chloride salt; S4: dilute Acid recovery: the mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation. When the aluminum chloride concentration is ≥80g / L, an acid evaporation process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I; S5: medium-concentrated acid recovery: the mixed solution of aluminum chloride and ferric chloride in S3 is recycled in S3 after acid supplementation. When the aluminum chloride concentration is ≥110g / L, an acid recovery process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I and recovered acid, and the recovered acid is returned to S3 for recycling; S6: suspension roasting: the deep desiliconized fly ash obtained in S3 is dried, dispersed and dried, and then sent to a gaseous suspension roasting furnace for short-time rapid roasting to obtain aluminum silicon oxide with low impurity content.
[0006] As a preferred solution, the average particle size of the high-alumina fly ash is 20-100 μm.
[0007] As a preferred solution, the average particle size of the high-alumina fly ash is 30-80 μm.
[0008] As a preferred solution, the volume ratio of the high-alumina fly ash and the sodium hydroxide solution is (1-1.5): (3-10).
[0009] As a preferred solution, the volume ratio of the high-alumina fly ash to the sodium hydroxide solution is 1:(4-6).
[0010] As a preferred solution, the volume ratio of the high-alumina fly ash to the sodium hydroxide solution is 1:4.
[0011] As a preferred solution, the concentration of the sodium hydroxide solution is 5-30wt%.
[0012] As a preferred solution, the concentration of the sodium hydroxide solution is 10-20wt%.
[0013] As a preferred solution, the temperature of the atmospheric pressure pre-desiliconization reaction is 60-100°C.
[0014] As a preferred solution, the temperature of the atmospheric pressure pre-desiliconization reaction is 80-90°C.
[0015] As a preferred solution, the reaction time of the normal pressure pre-desiliconization reaction is 3 to 8 hours.
[0016] As a preferred solution, the reaction time of the normal pressure pre-desiliconization reaction is 4 hours.
[0017] As a preferred solution, the stirring rate of the atmospheric pressure pre-desiliconization reaction is 200-400 r / min.
[0018] As a preferred solution, the mass ratio of aluminum to silicon in the desiliconized fly ash is 1.8-2.5.
[0019] As a preferred solution, the dilute acid is at least one of dilute hydrochloric acid, dilute sulfuric acid, dilute acetic acid, dilute nitric acid, and dilute oxalic acid.
[0020] As a preferred solution, the dilute acid is dilute hydrochloric acid or dilute sulfuric acid.
[0021] As a preferred solution, the concentration of the dilute acid is 0.5-5wt%.
[0022] As a preferred solution, the concentration of the dilute acid is 2-4wt%.
[0023] As a preferred solution, the volume ratio of the desiliconized fly ash and the dilute acid is (1-1.5): (2-10).
[0024] As a preferred solution, the volume ratio of the desiliconized fly ash and the dilute acid is (1-1.2): (2.5-8).
[0025] As a preferred solution, the temperature of the sodium removal by thermal insulation is 50-95° C., and the sodium removal time is 0.5-4 h.
[0026] As a preferred solution, the temperature of the sodium removal by thermal insulation is 60-80° C., and the sodium removal time is 0.5-2 h.
[0027] As a preferred solution, the stirring rate of the thermal insulation sodium removal is 200~400r / min.
[0028] As a preferred solution, the aluminum-silicon mass ratio of the sodium-desiliconized fly ash is 1.8-2.2.
[0029] In the present application, the sodium removal process of S2 can effectively dissolve and remove the internal zeolite phase sodium aluminosilicate and calcium oxide of the desiliconized fly ash by controlling the dilute acid content, thereby greatly reducing the content of the two in the desiliconized fly ash, thereby greatly inhibiting the formation of silicate gel in the subsequent impurity removal process, thereby avoiding the adsorption and guidance of water by silicate gel during the washing process, and ultimately reducing the water content in the deeply desiliconized fly ash, thereby controlling the overall preparation efficiency of aluminum silicon oxide.
[0030] As a preferred solution, the medium-concentrated acid is medium-concentrated hydrochloric acid or medium-concentrated sulfuric acid.
[0031] As a preferred solution, the concentration of the concentrated acid is 12-20wt%.
[0032] As a preferred solution, the volume ratio of the sodium-desiliconized fly ash and the medium concentrated acid is (1-1.2): (3-6).
[0033] As a preferred solution, the volume ratio of the sodium-desiliconized fly ash to the concentrated acid is 1:(3-6).
[0034] As a preferred solution, the temperature of the atmospheric pressure impurity removal is 70-100° C., and the impurity removal time is 2-5 hours.
[0035] As a preferred solution, the temperature of the atmospheric pressure impurity removal is 75-90° C., and the impurity removal time is 3-4 hours.
[0036] As a preferred solution, the stirring rate of the atmospheric pressure impurity removal is 200-400 r / min.
[0037] As a preferred solution, the moisture content of the deeply desiliconized fly ash is 20-42wt%.
[0038] As a preferred solution, the aluminum-silicon mass ratio of the deep desiliconized fly ash is 1.8-1.95.
[0039] In this application, the impurity removal process of S3 can effectively improve the overall preparation efficiency of aluminum silicon oxide and the recovery rate of aluminum silicon. By controlling the concentration and ratio of the concentrated acid, the iron oxide and titanium oxide content in the desiliconized fly ash after sodium removal can be effectively removed, thereby greatly reducing the number of surface hydroxyl groups of solid particles in the overall desiliconized fly ash, greatly reducing the guiding and attractive effect of the surface hydroxyl groups of the particles on moisture, and realizing the precise dehydration of fly ash in different intermediates through the secondary graded impurity removal process, thereby greatly reducing the content of moisture and bound water particles that are difficult to separate during the preparation process, thereby greatly improving the preparation efficiency and the recovery rate of aluminum silicon.
[0040] As a preferred solution, the mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation, the amount of acid supplementation is 30-35wt%, and the acid concentration after acid supplementation is 2-4wt%.
[0041] As a preferred solution, the concentration of the high concentration mixed solution I of aluminum chloride salt and ferric chloride salt is ≥120 g / L.
[0042] As a preferred solution, the mixed solution of aluminum chloride salt and ferric chloride salt is recycled in S3 after acid supplementation, the amount of acid supplementation is 30-35wt%, and the acid concentration after acid supplementation is 12-20wt%.
[0043] As a preferred solution, the concentration of the high concentration mixed solution of aluminum chloride salt and ferric chloride salt Ⅱ is ≥180g / L.
[0044] As a preferred solution, the concentration of the recovered acid is 15-25wt%.
[0045] As a preferred solution, the deeply desiliconized fly ash has an alumina content of 45-60wt%, a silicon oxide content of 28-36wt%, and a total content of the alumina content of 88wt%.
[0046] As a preferred solution, the crystal water content of the deeply desiliconized fly ash is 2-5wt%.
[0047] As a preferred solution, the unburned carbon content of the deeply desiliconized fly ash is 1.5-5.2wt%.
[0048] As a preferred solution, the moisture content of the deeply desiliconized fly ash after drying and dispersion is 0.5-1.5wt%.
[0049] In this application, amorphous silicon oxide is preferentially extracted from high-aluminum fly ash to form desiliconized fly ash, and then sodium aluminosilicate is decomposed from the desiliconized fly ash under low-concentration hydrochloric acid conditions to reduce the formation of silica gel, and then different types of impurities are removed step by step under medium-concentration hydrochloric acid conditions, and then the acid recovery process is used to achieve the recycling of free acid to obtain deep impurity-removed desiliconized fly ash with low moisture content, and aluminum silicon oxide with high whiteness, low unburned carbon content and low total impurity content is obtained through gas suspension rapid roasting treatment; the overall process method can greatly realize the simultaneous utilization of aluminum and silicon resources in fly ash. The simultaneous extraction and utilization of alumina and silicon oxide in fly ash increases the utilization rate of the main components in fly ash by 1 times compared with the traditional extraction of alumina from fly ash; and the overall process flow is shortened and the reaction conditions are mild, reducing process energy consumption and costs. This process does not require separation of crystalline alumina and silica in fly ash. Both the alkaline and acid treatments in the process are carried out under normal pressure conditions. Compared with the process requiring a reactor, it greatly reduces the investment cost and the process cost of production operation.
[0050] On the other hand, the utilization rate of fly ash can be greatly improved, and through the graded impurity removal process, the precise moisture removal of the intermediate fly ash can be achieved, so that the moisture content of the intermediate fly ash is reduced by about 50%, thereby greatly improving the preparation efficiency of aluminum silicon oxide of the final roasted fly ash.
[0051] As a preferred solution, the roasting temperature of the gas suspension roasting furnace is 600-900°C.
[0052] As a preferred solution, the roasting temperature of the gas suspension roasting furnace is 700-850°C.
[0053] As a preferred solution, the roasting time of the gas suspension roasting furnace is 4 to 10 seconds.
[0054] As a preferred solution, the unburned carbon content of the aluminum silicon oxide is 0.05-0.2wt%.
[0055] As a preferred solution, the whiteness of the aluminum silicon oxide is ≥85.
[0056] The beneficial effects of this application are:
[0057] 1. The present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, which can simultaneously extract two substances, aluminum oxide and silicon oxide, from the fly ash, which not only makes up for the technical defects of the prior art, but also has a wide source of raw materials, low energy consumption and low production cost. Moreover, the high-aluminum fly ash adopts a normal pressure and low-temperature process, and does not need to be subjected to high-pressure temperature treatment such as high temperature and medium temperature. In the process of preparing the main product, the remaining components can be co-produced into mature industrial products, realizing 100% utilization of the high-aluminum fly ash and generating no secondary solid waste.
[0058] 2. The present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash. Through the sodium removal process of S2, the internal zeolite phase sodium aluminosilicate and calcium oxide of the desiliconized fly ash can be effectively dissolved and removed by controlling the dilute acid content, thereby greatly reducing the content of the two in the desiliconized fly ash, thereby greatly inhibiting the formation of silicate gel in the subsequent impurity removal process, thereby avoiding the adsorption and guidance of water by silicate gel during the washing process, and ultimately reducing the water content in the deeply desiliconized fly ash, thereby controlling the overall preparation efficiency of aluminum silicon oxide.
[0059] 3. The present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, and the impurity removal process of S3 can effectively improve the overall preparation efficiency of aluminum silicon oxide and the aluminum silicon recovery rate. By controlling the concentration and ratio of the concentrated acid, the iron oxide and titanium oxide content in the desiliconized fly ash after sodium removal can be effectively removed, thereby greatly reducing the number of surface hydroxyl groups of solid particles in the overall desiliconized fly ash, and greatly reducing the guiding and attractive effect of the surface hydroxyl groups of the particles on moisture. Through the secondary graded impurity removal process, the precise dehydration of fly ash in different intermediates is achieved, thereby greatly reducing the content of moisture and bound water particles that are difficult to separate during the preparation process, thereby greatly improving the preparation efficiency and aluminum silicon recovery rate.
[0060] 4. The present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, which preferentially extracts amorphous silicon oxide from high-aluminum fly ash to form desiliconized fly ash, and then decomposes sodium aluminosilicate from the desiliconized fly ash under low-concentration hydrochloric acid conditions to reduce the formation of silica gel, and then removes different types of impurities step by step under medium-concentration hydrochloric acid conditions, and then uses an acid recovery process to recycle free acid to obtain deeply impurity-removed desiliconized fly ash with a low moisture content, and then undergoes gaseous suspension rapid roasting treatment to obtain aluminum silicon oxide with high whiteness, low unburned carbon content, and low total impurity content; the overall process method can largely achieve the simultaneous utilization of aluminum and silicon resources in fly ash.
[0061] 5. This application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, which simultaneously extracts and utilizes alumina and silicon oxide from fly ash. Compared with the traditional method of extracting alumina from fly ash, the utilization rate of the main components in fly ash is increased by 1 times; the overall process flow is shortened and the reaction conditions are mild, which reduces process energy consumption and costs. This process does not require the separation of crystalline alumina and silicon oxide in fly ash, and both the alkaline and acid treatments in the process are carried out under normal pressure. Compared with the process that requires a reactor, it greatly reduces the investment cost and the process cost of production and operation.
[0062] 6. The present application provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, the utilization rate of the fly ash can be greatly improved, and through the graded impurity removal process, the precise removal of moisture from the intermediate fly ash is achieved, thereby reducing the moisture content of the intermediate fly ash by about 50%, thereby greatly improving the preparation efficiency of aluminum silicon oxide from the final roasted fly ash. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a schematic diagram of the process flow of the method for preparing aluminum silicon oxide using high-aluminum fly ash in this application.
[0064] Figure 2 The XRD spectra of high-aluminum fly ash, desiliconized fly ash, sodium-desiliconized fly ash and aluminum-silicon oxide in Example 1 are shown.
[0065] Figure 3 This is the SEM spectrum of the high-alumina fly ash in Example 1.
[0066] Figure 4 This is the SEM image of the desiliconized fly ash in Example 1.
[0067] Figure 5 This is the SEM image of the fly ash with sodium and silicon removed in Example 1.
[0068] Figure 6 This is the SEM image of the deeply desiliconized fly ash in Example 1. DETAILED DESCRIPTION
[0069] The following will further explain and demonstrate the technical solutions in the above application content of this application in the form of specific implementation plans. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the application content of this application should be included in the scope to be protected by this application.
[0070] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0071] Example 1
[0072] Embodiment 1 The first aspect provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, the steps comprising: S1: pre-desiliconization of high-aluminum fly ash at normal pressure: the high-aluminum fly ash is subjected to normal pressure pre-desiliconization reaction with sodium hydroxide solution, the solution after the reaction is filtered, washed and separated, the solid phase is desiliconized fly ash, and the liquid phase is desiliconized alkali solution; S2: sodium removal: the desiliconized fly ash is mixed with dilute acid and then kept warm to remove sodium, after the sodium removal is completed, the solid phase is sodium-removed desiliconized fly ash, and the liquid phase is a mixed salt solution of aluminum chloride, calcium chloride and sodium chloride; S3: impurity removal: the sodium-removed desiliconized fly ash is mixed with medium-concentrated acid and then subjected to normal pressure impurity removal, after the completion of the impurity removal, the solid phase is deep desiliconized fly ash, and the liquid phase is a mixed solution of aluminum chloride salt and ferric chloride salt; S4: dilute acid return Recovery: The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation. When the aluminum chloride concentration is ≥80g / L, an acid evaporation process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I; S5: medium-concentrated acid recovery: The mixed solution of aluminum chloride and ferric chloride in S3 is recycled in S3 after acid supplementation. When the aluminum chloride concentration is ≥110g / L, an acid recovery process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I and recovered acid, and the recovered acid is returned to S3 for recycling; S6: suspension roasting: The deep desiliconized fly ash obtained in S3 is dried, dispersed and dried, and then sent to a gaseous suspension roasting furnace for short-time rapid roasting to obtain aluminum silicon oxide with low impurity content.
[0073] Process flow chart Figure 1 shown.
[0074] The XRD spectra of high-aluminum fly ash, desiliconized fly ash, sodium-desiliconized fly ash and aluminum-silicon oxide in this embodiment are as follows: Figure 2 shown.
[0075] The SEM spectrum of high-alumina fly ash is as follows: Figure 3 shown.
[0076] Among them, the high-alumina fly ash comes from a thermal power plant in Ordos, Inner Mongolia. The high-alumina fly ash includes Al2O3: 46.23%, SiO2: 41.54%, Fe2O3: 2.08%, CaO: 3.45%, Na2O: 0.21%, TiO2: 1.72%, unburned carbon: 4.67%, and the remainder is ash impurities.
[0077] The particle sizes of high-alumina fly ash are D10: 7.96μm, D50: 35.81μm, and D90: 89.62μm.
[0078] The volume ratio of high-alumina fly ash and sodium hydroxide solution is 1:4.
[0079] The concentration of the sodium hydroxide solution is 14.5 wt %.
[0080] The temperature of the atmospheric pressure pre-desiliconization reaction is 90°C, the atmospheric pressure pre-desiliconization time is 3h, and the stirring rate of the atmospheric pressure pre-desiliconization reaction is 300r / min.
[0081] The solution after the reaction was filtered, washed and separated, and the mass ratio of high-aluminum fly ash to washing water was 1.05:1.
[0082] The obtained desiliconized fly ash has Al2O3: 56.21%, SiO2: 27.92%, Fe2O3: 2.07%, CaO: 3.92%, Na2O: 1.97%, TiO2: 1.92%, unburned carbon: 5.27%, and the remainder is ash impurities; the moisture content of the deeply desiliconized fly ash is 48.26%. The aluminum-silicon mass ratio of the desiliconized fly ash is 2.01.
[0083] The SEM spectrum of desiliconized fly ash is as follows: Figure 4 shown.
[0084] The diluted acid is diluted hydrochloric acid with a concentration of 2wt%. The volume ratio of desiliconized fly ash to the diluted acid is 1:7.
[0085] The temperature of the heat preservation and sodium removal after the desiliconized fly ash is mixed with the dilute acid is 70° C., the sodium removal time is 1.5 hours, and the stirring rate is 400 r / min.
[0086] The sodium-desiliconized fly ash contains Al2O3: 59.12%, SiO2: 29.66%, Fe2O3: 1.92%, CaO: 0.32%, Na2O: 0.11%, TiO2: 1.85%, unburned carbon: 5.14%, and the remainder is ash impurities. The moisture content of the deep desiliconized fly ash is 41.33%. The aluminum-silicon mass ratio of the sodium-desiliconized fly ash is 1.99.
[0087] The SEM spectrum of fly ash with sodium removal and desiliconization is as follows: Figure 5 shown.
[0088] The medium-concentrated acid is medium-concentrated hydrochloric acid, and the concentration is 20wt%; the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:6.
[0089] The temperature for atmospheric pressure impurity removal is 70°C, the impurity removal time is 3h, and the stirring rate for atmospheric pressure impurity removal is 350r / min.
[0090] After the filtration and washing are completed, the weight ratio of the solid phase after atmospheric pressure impurity removal to the washing water is 1:1.6.
[0091] Deep desiliconized fly ash contains Al2O3: 57.81%, SiO2: 31.23%, Fe2O3: 0.37%, CaO: 0.11%, Na2O: 0.09%, TiO2: 1.45%, unburned carbon: 5.05%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 41.33%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.85.
[0092] SEM images of deep desiliconized fly ash are shown in Figure 2. Figure 6 shown.
[0093] The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 2wt%.
[0094] After the acid evaporation step, the concentration of the obtained high-concentration mixed solution I of aluminum chloride salt and ferric chloride salt is 127.8 g / L.
[0095] The mixed solution of aluminum chloride salt and ferric chloride salt is recycled in S3 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 13.5wt%.
[0096] After the acid recovery step, the concentration of the obtained high-concentration mixed solution of aluminum chloride salt and ferric chloride salt ⅠⅠ is 205.9 g / L, and the concentration of the recovered acid is 16.8 wt % hydrochloric acid.
[0097] The crystal water content of deeply desiliconized fly ash is 2.4wt%.
[0098] The moisture content of deeply desiliconized fly ash after drying and dispersion is 1.1wt%.
[0099] The dried material was put into a gas suspension calciner and calcined at 850°C for 3 seconds. The aluminum silicon oxide obtained after discharge had a whiteness of 87 and an unburned carbon content of 0.08%. The chemical composition of the aluminum silicon oxide was (Al2O3: 62.86%, SiO2: 34.05%, Fe2O3: 0.40%, CaO: 0.12%, Na2O: 0.10%, TiO2: 1.58%, and the remainder was ash impurities).
[0100] Example 2
[0101] Embodiment 2 The first aspect provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, the steps comprising: S1: pre-desiliconization of high-aluminum fly ash at normal pressure: the high-aluminum fly ash is subjected to a pre-desiliconization reaction at normal pressure with a sodium hydroxide solution, and the solution after the reaction is filtered, washed and separated, and the solid phase is desiliconized fly ash, and the liquid phase is a desiliconized alkali solution; S2: sodium removal: the desiliconized fly ash is mixed with a dilute acid and then kept warm to remove the sodium, and after the sodium removal is completed, the solid phase is the sodium-removed desiliconized fly ash, and the liquid phase is a mixed salt solution of aluminum chloride, calcium chloride and sodium chloride; S3: impurity removal: the sodium-removed desiliconized fly ash is mixed with a medium-concentrated acid and then subjected to atmospheric impurity removal, and after the completion of the impurity removal, the solid phase is deep desiliconized fly ash, and the liquid phase is a mixed solution of aluminum chloride salt and ferric chloride salt; S4: dilute acid return Recovery: The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation. When the aluminum chloride concentration is ≥80g / L, an acid evaporation process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I; S5: medium-concentrated acid recovery: The mixed solution of aluminum chloride and ferric chloride in S3 is recycled in S3 after acid supplementation. When the aluminum chloride concentration is ≥110g / L, an acid recovery process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I and recovered acid, and the recovered acid is returned to S3 for recycling; S6: suspension roasting: The deep desiliconized fly ash obtained in S3 is dried, dispersed and dried, and then sent to a gaseous suspension roasting furnace for short-time rapid roasting to obtain aluminum silicon oxide with low impurity content.
[0102] Among them, the high-alumina fly ash comes from a thermal power plant in Ordos, Inner Mongolia. The high-alumina fly ash includes Al2O3: 46.23%, SiO2: 41.54%, Fe2O3: 2.08%, CaO: 3.45%, Na2O: 0.21%, TiO2: 1.72%, unburned carbon: 4.67%, and the remainder is ash impurities.
[0103] The particle sizes of high-alumina fly ash are D10: 7.96μm, D50: 35.81μm, and D90: 89.62μm.
[0104] The volume ratio of high-alumina fly ash and sodium hydroxide solution is 1:7.
[0105] The concentration of the sodium hydroxide solution is 8.5wt%.
[0106] The temperature of the atmospheric pressure pre-desiliconization reaction is 70°C, the atmospheric pressure pre-desiliconization time is 8h, and the stirring rate of the atmospheric pressure pre-desiliconization reaction is 400r / min.
[0107] The solution after the reaction is filtered, washed and separated, and the mass ratio of high-aluminum fly ash to washing water is 1.2:1.
[0108] The obtained desiliconized fly ash has Al2O3: 54.18%, SiO2: 29.37%, Fe2O3: 2.16%, CaO: 3.85%, Na2O: 2.69%, TiO2: 1.88%, unburned carbon: 5.18%, and the remainder is ash impurities. The moisture content of the deep desiliconized fly ash is 50.27%. The aluminum-silicon mass ratio of the desiliconized fly ash is 1.84.
[0109] The diluted acid is diluted hydrochloric acid with a concentration of 5wt%. The volume ratio of desiliconized fly ash to the diluted acid is 1:6.
[0110] The temperature of the heat preservation and sodium removal after the desiliconized fly ash is mixed with the dilute acid is 50° C., the sodium removal time is 4 hours, and the stirring rate is 400 r / min.
[0111] The sodium-desiliconized fly ash contains Al2O3: 56.76%, SiO2: 31.23%, Fe2O3: 1.96%, CaO: 0.21%, Na2O: 0.10%, TiO2: 1.82%, unburned carbon: 5.02%, and the remainder is ash impurities. The moisture content of the deeply desiliconized fly ash is 40.13%. The aluminum-silicon mass ratio of the sodium-desiliconized fly ash is 1.82.
[0112] The medium-concentrated acid is medium-concentrated hydrochloric acid, and the concentration is 20wt%; the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:6.
[0113] The temperature for atmospheric pressure impurity removal is 70°C, the impurity removal time is 3h, and the stirring rate for atmospheric pressure impurity removal is 350r / min.
[0114] After the filtration and washing are completed, the weight ratio of the solid phase after atmospheric pressure impurity removal to the washing water is 1:1.8.
[0115] Deep desiliconized fly ash contains Al2O3: 54.78%, SiO2: 33.12%, Fe2O3: 0.45%, CaO: 0.13%, Na2O: 0.10%, TiO2: 1.53%, unburned carbon: 5.02%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 39.33%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.85.
[0116] The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 5wt%.
[0117] After the acid evaporation step, the concentration of the obtained high-concentration mixed solution I of aluminum chloride salt and ferric chloride salt is 135.2 g / L.
[0118] The mixed solution of aluminum chloride salt and ferric chloride salt is recycled in S3 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 20wt%.
[0119] After the acid recovery step, the concentration of the obtained high-concentration mixed solution of aluminum chloride salt and ferric chloride salt ⅠⅠ is 186.9 g / L, and the concentration of the recovered acid is 22.1 wt% hydrochloric acid.
[0120] The crystal water content of deeply desiliconized fly ash is 2.1wt%.
[0121] The moisture content of the deeply desiliconized fly ash after drying and dispersion is 0.9wt%.
[0122] The dried material was put into a gas suspension calciner and calcined at 850°C for 5 seconds. The aluminum silicon oxide obtained after discharge had a whiteness of 89 and an unburned carbon content of 0.12%. The chemical composition of the aluminum silicon oxide was (Al2O3: 60.32%, SiO2: 36.51%, Fe2O3: 0.50%, CaO: 0.14%, Na2O: 0.11%, TiO2: 1.68%, and the remainder was ash impurities).
[0123] Example 3
[0124] Embodiment 3 The first aspect provides a method for preparing aluminum silicon oxide using high-aluminum fly ash, the steps comprising: S1: pre-desiliconization of high-aluminum fly ash at normal pressure: the high-aluminum fly ash is subjected to a pre-desiliconization reaction at normal pressure with a sodium hydroxide solution, and the solution after the reaction is filtered, washed and separated, and the solid phase is desiliconized fly ash, and the liquid phase is a desiliconized alkali solution; S2: sodium removal: the desiliconized fly ash is mixed with a dilute acid and then kept warm to remove the sodium, and after the sodium removal is completed, the solid phase is the sodium-removed desiliconized fly ash, and the liquid phase is a mixed salt solution of aluminum chloride, calcium chloride and sodium chloride; S3: impurity removal: the sodium-removed desiliconized fly ash is mixed with a medium-concentrated acid and then subjected to atmospheric impurity removal, and after the completion of the impurity removal, the solid phase is deep desiliconized fly ash, and the liquid phase is a mixed solution of aluminum chloride salt and ferric chloride salt; S4: dilute acid return Recovery: The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation. When the aluminum chloride concentration is ≥80g / L, an acid evaporation process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I; S5: medium-concentrated acid recovery: The mixed solution of aluminum chloride and ferric chloride in S3 is recycled in S3 after acid supplementation. When the aluminum chloride concentration is ≥110g / L, an acid recovery process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I and recovered acid, and the recovered acid is returned to S3 for recycling; S6: suspension roasting: The deep desiliconized fly ash obtained in S3 is dried, dispersed and dried, and then sent to a gaseous suspension roasting furnace for short-time rapid roasting to obtain aluminum silicon oxide with low impurity content.
[0125] Among them, the high-alumina fly ash comes from a thermal power plant in Ordos, Inner Mongolia. The high-alumina fly ash includes Al2O3: 46.23%, SiO2: 41.54%, Fe2O3: 2.08%, CaO: 3.45%, Na2O: 0.21%, TiO2: 1.72%, unburned carbon: 4.67%, and the remainder is ash impurities.
[0126] The particle sizes of high-alumina fly ash are D10: 7.96μm, D50: 35.81μm, and D90: 89.62μm.
[0127] The volume ratio of high-alumina fly ash and sodium hydroxide solution is 1:4.
[0128] The concentration of the sodium hydroxide solution is 15wt%.
[0129] The temperature of the atmospheric pressure pre-desiliconization reaction is 80°C, the atmospheric pressure pre-desiliconization time is 4h, and the stirring rate of the atmospheric pressure pre-desiliconization reaction is 400r / min.
[0130] The solution after the reaction is filtered, washed and separated, and the mass ratio of high-aluminum fly ash to washing water is 0.9:1.
[0131] The obtained desiliconized fly ash has Al2O3: 57.12%, SiO2: 27.45%, Fe2O3: 2.22%, CaO: 3.89%, Na2O: 1.62%, TiO2: 1.82%, unburned carbon: 4.92%, and the remainder is ash impurities. The moisture content of the deep desiliconized fly ash is 48.59%. The aluminum-silicon mass ratio of the desiliconized fly ash is 2.08.
[0132] The diluted acid is diluted hydrochloric acid with a concentration of 3wt%. The volume ratio of desiliconized fly ash to the diluted acid is 1:4.
[0133] The temperature of the heat preservation and sodium removal after the desiliconized fly ash is mixed with the dilute acid is 70° C., the sodium removal time is 1 hour, and the stirring rate is 400 r / min.
[0134] The sodium-desiliconized fly ash contains Al2O3: 59.13%, SiO2: 29.16%, Fe2O3: 2.01%, CaO: 0.12%, Na2O: 0.08%, TiO2: 1.89%, unburned carbon: 5.18%, and the remainder is ash impurities. The moisture content of the deep desiliconized fly ash is 39.88%. The aluminum-silicon mass ratio of the sodium-desiliconized fly ash is 2.03.
[0135] The medium-concentrated acid is medium-concentrated hydrochloric acid with a concentration of 15wt%; the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:4.
[0136] The temperature of atmospheric pressure impurity removal is 90°C, the impurity removal time is 3h, and the stirring speed of atmospheric pressure impurity removal is 400r / min.
[0137] After the filtration and washing are completed, the weight ratio of the solid phase after atmospheric pressure impurity removal to the washing water is 1:1.5.
[0138] Deep desiliconized fly ash contains Al2O3: 58.04%, SiO2: 30.28%, Fe2O3: 0.32%, CaO: 0.12%, Na2O: 0.09%, TiO2: 1.41%, unburned carbon: 5.03%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 38.96%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.92.
[0139] The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 3wt%.
[0140] After the acid evaporation step, the concentration of the obtained high-concentration mixed solution I of aluminum chloride salt and ferric chloride salt is 129.1 g / L.
[0141] The mixed solution of aluminum chloride salt and ferric chloride salt is recycled in S3 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 15wt%.
[0142] After the acid recovery step, the concentration of the obtained high-concentration mixed solution of aluminum chloride salt and ferric chloride salt ⅠⅠ is 194.8 g / L, and the concentration of the recovered acid is 22.1 wt% hydrochloric acid.
[0143] The crystal water content of deeply desiliconized fly ash is 1.9wt%.
[0144] The moisture content of the deeply desiliconized fly ash after drying and dispersion is 1.2wt%.
[0145] The dried material was put into a gas suspension roasting furnace and roasted at 800°C for 2s. The aluminum silicon oxide obtained after discharge had a whiteness of 90 and an unburned carbon content of 0.08%. The chemical composition of the aluminum silicon oxide was (Al2O3: 63.90%, SiO2: 32.38%, Fe2O3: 0.35%, CaO: 0.13%, Na2O: 0.10%, TiO2: 1.55%, and the remainder was ash impurities).
[0146] Comparative Example 1
[0147] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that: S2 is not included, and the desiliconized fly ash obtained from S1 and 13.5wt% hydrochloric acid are directly mixed in a volume ratio of 1:4.5 for atmospheric pressure impurity removal. The temperature for atmospheric pressure impurity removal is 90°C, the impurity removal time is 6h, and the stirring rate for atmospheric pressure impurity removal is 400r / min.
[0148] After completion, the impurity-removed and desiliconized fly ash is obtained, including Al2O3: 56.88%, SiO2: 32.12%, Fe2O3: 0.40%, CaO: 0.12%, Na2O: 0.09%, TiO2: 1.47%, unburned carbon: 5.10%, and the remainder is ash impurities. The moisture content of the impurity-removed and desiliconized fly ash is 67.37%. The aluminum-silicon mass ratio of the impurity-removed and desiliconized fly ash is 1.85.
[0149] Comparative Example 2
[0150] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that: S2 is not included, and the desiliconized fly ash obtained from S1 and 13.5wt% hydrochloric acid are directly mixed in a volume ratio of 1:8 for atmospheric pressure impurity removal, the temperature for atmospheric pressure impurity removal is 90°C, the impurity removal time is 6h, and the stirring rate for atmospheric pressure impurity removal is 400r / min.
[0151] After completion, the impurity-removed and desiliconized fly ash is obtained, including Al2O3: 57.12%, SiO2: 31.96%, Fe2O3: 0.39%, CaO: 0.11%, Na2O: 0.09%, TiO2: 1.46%, unburned carbon: 5.09%, and the remainder is ash impurities. The moisture content of the impurity-removed and desiliconized fly ash is 62.17%. The aluminum-silicon mass ratio of the impurity-removed and desiliconized fly ash is 1.79.
[0152] Comparative Example 3
[0153] The specific implementation of this comparative example is basically the same as that of Example 1, except that the medium-concentrated acid is medium-concentrated hydrochloric acid with a concentration of 9.5wt%; and the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:2.5.
[0154] The temperature of atmospheric pressure impurity removal is 40°C, the impurity removal time is 3h, and the stirring speed of atmospheric pressure impurity removal is 200r / min.
[0155] Deep desiliconized fly ash contains Al2O3: 55.98%, SiO2: 32.79%, Fe2O3: 0.48%, CaO: 0.17%, Na2O: 0.12%, TiO2: 1.49%, unburned carbon: 5.07%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 64.23%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.71.
[0156] Comparative Example 4
[0157] The specific implementation of this comparative example is basically the same as that of Example 1, except that the dilute acid is dilute hydrochloric acid with a concentration of 0.45 wt %, and the volume ratio of desiliconized fly ash to dilute acid is 1:3.
[0158] The temperature of the heat preservation and sodium removal after the desiliconized fly ash is mixed with the dilute acid is 40° C., the sodium removal time is 1 hour, and the stirring rate is 200 r / min.
[0159] Deep desiliconized fly ash contains Al2O3: 56.42%, SiO2: 32.15%, Fe2O3: 0.46%, CaO: 0.16%, Na2O: 0.12%, TiO2: 1.48%, unburned carbon: 5.05%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 61.19%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.75.
[0160] Comparative Example 5
[0161] The specific implementation of this comparative example is basically the same as that of Example 1, except that:
[0162] The medium-concentrated acid is medium-concentrated acetic acid, and the concentration of the medium-concentrated acid is 35wt%.
[0163] Deep desiliconized fly ash contains Al2O3: 57.23%, SiO2: 30.25%, Fe2O3: 0.37%, CaO: 0.12%, Na2O: 0.11%, TiO2: 1.51%, unburned carbon: 5.06%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 63.25%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.89.
[0164] Comparative Example 6
[0165] The specific implementation of this comparative example is basically the same as that of Example 1, except that:
[0166] The medium-concentrated acid is medium-concentrated nitric acid, and the concentration is 10.5wt%; the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:10.
[0167] Deep desiliconized fly ash contains 57.87%, SiO2: 30.16%, Fe2O3: 0.35%, CaO: 0.11%, Na2O: 0.10%, TiO2: 1.46%, unburned carbon: 5.02%, and the remainder is ash impurities. The moisture content of deep desiliconized fly ash is 59.87%. The aluminum-silicon mass ratio of deep desiliconized fly ash is 1.92.
[0168] Performance Evaluation
[0169] The moisture content of the fly ash after the impurity removal process in the embodiments and comparative examples, the whiteness of the final aluminum silicon oxide, the unburned carbon content, and the aluminum oxide and silicon oxide content data results are recorded in Table 1.
[0170] Table 1 Performance evaluation results
[0171]
[0172] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that the method for preparing aluminum silicon oxide using high-aluminum fly ash provided in the present application has excellent high-aluminum fly ash utilization rate. Compared with the traditional fly ash extraction of alumina, the utilization rate of the main components in the fly ash is increased by 1 times; and the overall process flow is shortened and the reaction conditions are mild, which reduces the process energy consumption and cost; and through graded acid treatment, accurate moisture removal of the intermediate fly ash is achieved, thereby reducing the moisture content of the intermediate fly ash by about 50%, thereby greatly improving the preparation efficiency of aluminum silicon oxide of the final roasted fly ash.
Claims
1. A method for preparing aluminum silicon oxide using high-aluminum fly ash, characterized in that: The steps include: S1: pre-desiliconization of high-aluminum fly ash at normal pressure: the high-aluminum fly ash is subjected to a pre-desiliconization reaction at normal pressure with a sodium hydroxide solution, and the solution after the reaction is filtered, washed and separated, and the solid phase is desiliconized fly ash, and the liquid phase is desiliconized alkali solution; S2: sodium removal: the desiliconized fly ash is mixed with dilute acid and then kept warm to remove sodium, and after the sodium removal is completed, the solid phase is sodium-desiliconized fly ash, and the liquid phase is a mixed salt solution of aluminum chloride, calcium chloride and sodium chloride; S3: impurity removal: the sodium-desiliconized fly ash is mixed with medium-concentrated acid and then subjected to impurity removal at normal pressure, and after the impurity removal is completed, it is filtered and washed, and after the impurity removal is completed, the solid phase is deep desiliconized fly ash, and the liquid phase is a mixed solution of aluminum chloride salt and ferric chloride salt; S4: dilute acid recovery: aluminum chloride, calcium chloride and sodium chloride are mixed and then washed. The salt solution is recycled in S2 after acid supplementation. When the aluminum chloride concentration is ≥80g / L, an acid evaporation process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I; S5: medium-concentrated acid recovery: the mixed solution of aluminum chloride and ferric chloride in S3 is recycled in S3 after acid supplementation. When the aluminum chloride concentration is ≥110g / L, an acid recovery process is performed to obtain a high-concentration mixed solution of aluminum chloride and ferric chloride I and recovered acid, and the recovered acid is returned to S3 for recycling; S6: suspension roasting: the deep desiliconized fly ash obtained in S3 is dried, scattered and dried, and then sent to a gaseous suspension roasting furnace for short-time rapid roasting to obtain aluminum silicon oxide with low impurity content; The composition of the high-aluminum fly ash is: Al2O3: 46.23%, SiO2: 41.54%, Fe2O3: 2.08%, CaO: 3.45%, Na2O: 0.21%, TiO2: 1.72%, unburned carbon: 4.67%, and the balance is ash impurities; The particle sizes of the high-alumina fly ash are D10: 7.96 μm, D50: 35.81 μm, and D90: 89.62 μm; The volume ratio of the high-alumina fly ash to the sodium hydroxide solution is 1:4; The concentration of the sodium hydroxide solution is 14.5wt%; The temperature of the atmospheric pressure pre-desiliconization reaction is 90°C, the atmospheric pressure pre-desiliconization time is 3h; the stirring rate of the atmospheric pressure pre-desiliconization reaction is 300r / min; The solution after the reaction is filtered, washed and separated, and the mass ratio of high-aluminum fly ash to washing water is 1.05:1; The obtained desiliconized fly ash has Al2O3: 56.21%, SiO2: 27.92%, Fe2O3: 2.07%, CaO: 3.92%, Na2O: 1.97%, TiO2: 1.92%, unburned carbon: 5.27%, and the remainder is ash impurities; the moisture content of the deeply desiliconized fly ash is 48.26%; the aluminum-silicon mass ratio of the desiliconized fly ash is 2.01; The dilute acid is dilute hydrochloric acid with a concentration of 2wt%; the volume ratio of desiliconized fly ash to the dilute acid is 1:7; The temperature of the desiliconized fly ash and the diluted acid for the sodium removal is 70°C, the sodium removal time is 1.5h, and the stirring rate is 400r / min; The sodium-desiliconized fly ash contains 59.12% Al2O3, 29.66% SiO2, 1.92% Fe2O3, 0.32% CaO, 0.11% Na2O, 1.85% TiO2, 5.14% unburned carbon, and the remainder is ash impurities. The moisture content of the deep desiliconized fly ash is 41.33%; the aluminum-silicon mass ratio of the sodium-desiliconized fly ash is 1.99; The medium-concentrated acid is medium-concentrated hydrochloric acid with a concentration of 20wt%; the volume ratio of the sodium-desiliconized fly ash to the medium-concentrated acid is 1:6; The temperature of the atmospheric pressure impurity removal is 70°C, the impurity removal time is 3h, and the stirring speed of the atmospheric pressure impurity removal is 350r / min; In the filtering and washing after completion, the weight ratio of the solid phase after atmospheric pressure impurity removal to the washing water is 1:1.6; The deep desiliconized fly ash has Al2O3: 57.81%, SiO2: 31.23%, Fe2O3: 0.37%, CaO: 0.11%, Na2O: 0.09%, TiO2: 1.45%, unburned carbon: 5.05%, and the balance is ash impurities. The moisture content of the deep desiliconized fly ash is 41.33%; the aluminum-silicon mass ratio of the deep desiliconized fly ash is 1.85; The mixed salt solution of aluminum chloride, calcium chloride and sodium chloride is recycled in S2 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 2wt%; After the acid evaporation step, the concentration of the obtained high-concentration aluminum chloride salt and ferric chloride salt mixed solution I is 127.8 g / L; The mixed solution of aluminum chloride salt and ferric chloride salt is recycled in S3 after acid supplementation, the amount of acid supplementation is 31wt%, and the acid concentration after acid supplementation is 13.5wt%; After the acid recovery step, the concentration of the obtained high-concentration mixed solution of aluminum chloride salt and ferric chloride salt ⅠⅠ is 205.9 g / L, and the concentration of the recovered acid is 16.8 wt% hydrochloric acid; The crystal water content of the deep desiliconized fly ash is 2.4wt%; The moisture content of the deep desiliconized fly ash after drying and breaking up is 1.1wt%; The dried material is put into a gas suspension calciner and calcined at 850°C for 3 seconds. The aluminum silicon oxide obtained after discharge has a whiteness of 87 and an unburned carbon content of 0.08%. The chemical composition of the aluminum silicon oxide is: Al2O3: 62.86%, SiO2: 34.05%, Fe2O3: 0.40%, CaO: 0.12%, Na2O: 0.10%, TiO2: 1.58%, and the remainder is ash impurities.
Citation Information
Patent Citations
Method for producing mullite and calcium silicate by using high-alumina fly ash
CN102583409A
Method for preparing mullite through carrying out two-stage acid treatment on high-alumina fly ash
CN104671811A
Method for wet-process extraction of alumina from high-aluminum fly ash
CN106145169A
Method for in-situ synthesis of high-strength low-thermal-conductivity porous mullite ceramic by pretreatment of high-alumina fly ash
CN115448708A
Method for preparing high-alumina-silica-ratio low-impurity primary crystal mullite from high-alumina fly ash
CN116282053A
